Judging Factor Abundance - Bowen, H. P.; Sveikauskas, L. (Quarterly Journal of Economics, 1992)
Recent theory casts doubt on the frequently used interindustry regression method of inferring a country's abundant factors. This paper examines the empirical importance of these theoretical qualifications by comparing regression-derived estimates of factor abundance with both revealed and actual factor abundances for 35 countries and 12 resources. We demonstrate the theoretical importance of trade imbalances for the reliability of the regression estimates and therefore propose and implement a theoretically consistent trade imbalance correction. The results indicate that, despite valid theoretical concerns, the regression estimates are generally reliable indicators of revealed factor abundance. Therefore, the innumerable regression studies conducted over the past 30 years can be considered to provide reliable evidence concerning the validity of the factor abundance theory.